1981
DOI: 10.1182/blood.v58.1.122.122
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of transfusion-related alloimmunization in intensively treated cancer patients

Abstract: A retrospective review of HLA antibody testing and transfusion records of 100 cancer patients who required extensive platelet support revealed that 27 of 100 patients exhibited positive HLA antibody tests; only 13 remained positive on repetitive examination, while 88% of aplastic anemia patients so tested were positive. Sixty-five patients with leukemia, 16 with Ewing's sarcoma, and 19 with recurrent undifferentiated lymphoma were studied. Each patient received at least 10 U of platelets (mean of 72). HLA anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
27
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 19 publications
3
27
1
Order By: Relevance
“…These data suggest that there seems to be no enhanced RBC alloimmunization in patients with malaria. Absence of alloimmunization as a result of immunosuppressive effects of AIDS or anti-cancer chemotherapy has been reported in previous studies [20,26]. However, in this study 5 (55AE6%) of the 9 alloimmunized patients with cancer had been receiving anti-cancer chemotherapy.…”
Section: Discussionsupporting
confidence: 53%
“…These data suggest that there seems to be no enhanced RBC alloimmunization in patients with malaria. Absence of alloimmunization as a result of immunosuppressive effects of AIDS or anti-cancer chemotherapy has been reported in previous studies [20,26]. However, in this study 5 (55AE6%) of the 9 alloimmunized patients with cancer had been receiving anti-cancer chemotherapy.…”
Section: Discussionsupporting
confidence: 53%
“…HLA antibodies may disappear over time, even in the presence of continued transfusions. 21,[46][47][48][49][50][62][63][64] Our data indicated that a decrease in PRA level occurred in 11 (31.4%) of 35 patients tested at least 28 days after initial testing. If one were not aware of the change in PRA level and continued to select platelets on the basis of initial testing, that would not adversely affect patient care, although it might result in an unnecessary selection of a matched or selected platelet component.…”
Section: Discussionmentioning
confidence: 58%
“…5 Yet in bone marrow transplant patients, patients with solid tumors, and patients with AIDS, the rate of D alloimmunization in D− patients after transfusion with D+ blood was less than 10%. [6][7][8][9] These rates certainly suggest that increasing immunologic compromise affects the incidence of D alloimmunization. 4,5 Anti-D, however, remains significant for females of child-bearing potential: 20% of pregnancies where maternal anti-D is detectable will have severe hemolytic disease of the newborn.…”
mentioning
confidence: 99%